2017
DOI: 10.1002/mp.12566
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of beam arrangements in proton minibeam radiotherapy by cell survival simulations

Abstract: Purpose: Proton minibeam radiotherapy using submillimeter beam dimensions allows to enhance tissue sparing in the entrance channel by spatial fractionation additionally to advantageous proton depth dose distribution. In the entrance channel, spatial fractionation leads to reduced side effects compared to conventional proton therapy. The submillimeter sized beams widen with depth due to small angle scattering and enable therefore, in contrary to x-ray microbeam radiation therapy (MRT), the homogeneous irradiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 30 publications
0
41
0
Order By: Relevance
“…Results illustrate that the lateral homogeneity of the dose at the Bragg peak is closely correlated with the center‐to‐center (ctc) value and the initial energy of the beam, thereby influencing the design of the multislit collimator, as increasing the ctc significantly increases the PVDR in normal tissues. Very recently, the beam size variations as well as lateral and in‐depth‐dose homogeneity were characterized as a function of the inter‐slit distance for theoretically focused high‐energy proton pencil beams and various beam arrangements. Using initial beam size of σ = 0.2 mm, these authors found optimal ctc values comparable to those reported in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Results illustrate that the lateral homogeneity of the dose at the Bragg peak is closely correlated with the center‐to‐center (ctc) value and the initial energy of the beam, thereby influencing the design of the multislit collimator, as increasing the ctc significantly increases the PVDR in normal tissues. Very recently, the beam size variations as well as lateral and in‐depth‐dose homogeneity were characterized as a function of the inter‐slit distance for theoretically focused high‐energy proton pencil beams and various beam arrangements. Using initial beam size of σ = 0.2 mm, these authors found optimal ctc values comparable to those reported in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…72 Alternative materials that have been proposed to reduce the neutron dose by approximately 30% include nickel, iron and brass. 73 The most sophisticated framework to obtain optimal irradiation geometry was recently presented by Sammer et al 63 They defined the incident beam geometry and energy within an elegant inverse planning approach and evaluated the effectiveness of different beam geometries in terms of survival fractions. The overall aim was to optimize the geometry and distances between the minibeams to minimize overall cell killing outside the target, while maintaining uniform dose coverage at depth.…”
Section: Feasibility Of Uniform Target Irradiationmentioning
confidence: 99%
“…1 The aim in SFRT was to spare normal tissue by depositing dose in spatially fractionated manner, but at the same time deliver homogeneous dose to tumor volume. 2 One of the metrics of how good SFRT is achieved is the peak-tovalley-dose ratio (PVDR), of which the "peak dose" refers to the radiation dose of an exposed region and the "valley dose" refers to the dose of the adjacent unexposed region. It has been shown that high PVDRs and low valley doses tend to increase normal tissue sparing.…”
Section: Introductionmentioning
confidence: 99%